Derivatives Usage, Operational Hedge and Exchange Rate Regime: Evidence from Chinese Firms - WU, Mingming (2010)
In 2005, China liberalized its foreign exchange regime, and allows its currency Renminbi (RMB) to fluctuate within a managed band width. This important economic event exposes Chinese firms to considerable foreign exchange risk. The aim of this study is to analyze the relationship between the new exchange rate regime and firm’s risk management strategy. The study uses a sample of 30 Chinese firms listed in Hong Kong Stock Exchange. The use of foreign currency derivatives and operational hedging are investigated simultaneously. The information on the derivatives usage and currency composition of debt and assets and revenues are extracted from the footnotes of firms’ annual reports from 2004 to 2007. The study observes that neither more Chinese firms use foreign currency derivatives, nor a matching took place after the introduction of a managed floating exchange rate regime. Further investigation has been made by comparing the differences of firm-level characteristics between hedgers and non-hedgers. The evidence shows firms with smaller size and higher foreign revenue tend to hedge. The findings are inconsistent with the hypothesis that large firms tend to hedge and firms with higher foreign revenue are likely to leave foreign currency liabilities un-hedged. The finding supports the hypothesis that hedging positively linked with the level of foreign debt. Five sets of explanation are proposed. First, the rigidity of RMB exchange rate may hinder the exchange-rate hedging. Second, it may be the issue of the depth of market that precludes firms from using foreign currency derivatives extensively. Third, the phenomenon of one-way-bet that strong expectation to RMB appreciation may fuel firms in engaging the game of mismatch. Forth, it can be the ownership of firms, i.e. state- owned enterprises (SOEs) in the study impacts the finding. Finally, it can be attribute to institutional problem, such as unfamiliarity to the currency derivatives, or lacking institutional service. The research ends with a short discussion on limitations of the current study and highlights insight shall be further explored in this field.